Palliative management for malignant biliary obstruction and gastric outlet obstruction from pancreatic cancer - Pengfei Wu; Kai Chen; Jin He (Annals of Gastroenterological Surgery)
Abstract Pancreatic cancer is among the leading causes of gastrointestinal cancer‐related death, with a dismal prognosis. Over 80% of pancreatic cancer patients present with advanced disease, making curative resection unfeasible. These patients are often presented with malignant biliary obstruction (MBO) and gastric outlet obstruction (GOO). In these cases, palliative management is aimed to alleviate symptoms, enhance quality of life, and facilitate subsequent chemotherapy. Currently, neoadjuvant chemotherapy is frequently used in both borderline resectable and resectable pancreatic cancer, necessitating effective biliary and gastrointestinal drainage in a growing number of patients. Traditionally, surgical bypass was the gold standard, performed via either a minimally invasive or open approach. However, notable progress has emerged in developing endoscopic techniques, such as endoscopic retrograde cholangiopancreatography (ERCP) stenting for MBO and endoscopic enteral stenting for GOO. While these procedures provide rapid symptom relief, they are associated with higher stent dysfunction rates and more frequent re‐intervention needs. When ERCP fails, percutaneous transhepatic biliary drainage is a widely accepted alternative for MBO. Endoscopic ultrasound (EUS)‐guided techniques, including EUS‐guided biliary drainage and EUS‐guided gastroenterostomy, have recently gained prominence. Emerging clinical data suggest that these methods may be superior, potentially becoming the preferred first‐line palliative treatment for unresectable pancreatic cancer. This review will summarize the current evidence on managing MBO and GOO in patients with pancreatic cancer.